Effect of microbial inoculants on the storage characteristics and nutritional value of high moisture corn for finishing pigs - Bolsen, K.K.; Jones, D.B.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
High moisture corn (23% moisture) was harvested in September, 1988, and stored in concrete silos until March, 1989. As the corn was harvested, it was divided into four treatment silos: high moisture corn (HMC) and HMC treated with inoculants containing lactobacillus, serratia, or streptococcus organisms. As a positive control, some of the corn was allowed to "field dry" to 14% moisture before being harvested. Two hundred forty finishing pigs were fed the com treatments. Approximately mid-experiment, samples of the corn and mixed diets were collected and evaluated for aerobic stability. At the end of the experiment, chromic oxide was added to the diets (.25%), and the indirect method was used to calculate apparent dry matter and nitrogen digestibilities. Results from the experiment indicated that the mixed diets were stable for a longer period of time than the ground corn (132 h vs 103 h until heating occurred). The HMC treatment was the least stable, and lactobacillus-treated corn was less stable than corn treated with the serratia and streptococcus inoculants. Also, corn treated with the serratia inoculant was more stable than corn treated with the streptococcus inoculant. Average daily gain of pigs was not affected by corn treatment. There were no differences in dry matter intake or feed efficiency expressed on a dry matter basis. Apparent digestibilities of dry matter and nitrogen were similar among the treatment groups. From these data, we conclude that new experimental inoculants (serratia and streptococcus) improve the storage characteristics of high moisture corn. However, an improvement in storage characteristics does not necessarily indicate improved nutritional value of the treated corn.
Keywords: Swine; Microbial inoculants; Aerobic stability; Performance; Digestibility; Finishing pigs